A comparison of the response of diploid and triploid Atlantic salmon (Salmo salar) siblings to a commercial furunculosis vaccine and subsequent experimental infection with Aeromonas salmonicida. (October 2016) - Chalmers, Lynn; Thompson, Kim D.; Taylor, John F.; Black, Sean; Migaud, Herve; North, Ben; Adams, Alexandra
Abstract: Sterile triploid fish represent a solution to the problems associated with sexual maturation and escapees in aquaculture. However, as disease outbreaks continue to cause significant economic losses to the industry, it is essential that the response of triploids to disease and disease treatments be characterised. The aim of this study was to compare the response of triploid Atlantic salmon to a commercial furunculosis vaccine with that of diploid fish, and to assess the vaccine efficacy in the two ploidies through an experimental infection with Aeromonas salmonicida . Diploid and triploid Atlantic salmon were injected intraperitoneally with either phosphate buffered saline, liquid paraffin adjuvant or a commercial furunculosis vaccine. Following vaccination, growth, adhesion scores and a variety of assays to assess immune function, such as respiratory burst and antibody response, were measured. Vaccination did not have a significant effect on the weight of either ploidy prior to challenge at 750° days. Adhesion scores were significantly higher in vaccinated fish compared to unvaccinated fish, although no effect of ploidy was observed. Ploidy significantly affected respiratory burst activity following vaccination, however, with triploids exhibiting higher activity than diploids. Combined with lower white blood cell numbers observed in the triploids, it may be that this low cell number is compensated for by increased cellular activity. Ploidy however, did not have a significant effect on complement activity or antibody response, with significantly higher antibody levels detected in all vaccinated fish compared to unvaccinated controls. In addition, both ploidy groups were well protected following challenge with no difference in the relative percentage survival. Based on these results, it appears that ploidy does not affect the severity of adhesions that result post-vaccinate or in the fish's immune response following vaccination, and the furunculosis vaccine performs equally well in both diploid and triploid Atlantic salmon. Highlights: Commercial furunculosis vaccine effective in protecting triploid Atlantic salmon. Ploidy did not affect the severity of the adhesions occurring in vaccinated fish. Differences in immune response may due to compensatory mechanism in triploids.